Students creative thinking skills on differentiated instruction - Peni Anggareni; Akhmad Faisal Hidayat (International Journal of Trends in Mathematics Education Research, 2022)
Creative thinking is one of the skills that must be possessed by students in the 21st century. This study aims to investigate and describe students' creative thinking skills in completing the Cartesian Coordinate Skills Task (CCST). This research was conducted in one of the public junior high schools in Jambi City. The research subjects were six 8th grade junior high school students who have learnt by product differentiate instruction. The research subjects were divided into 3 categories based on the results of the Knowledge Question (KQ), namely high, medium, and low. Students' creative thinking skills were tested through CCST and the results were analyzed based on creative thinking indicators. The results of this study indicate that each subject tends to be able to show aspects of fluency and flexibility, but only three subjects are able to show aspects of novelty. In addition, from the three subjects, there is 1 subject in the low category who is able to show the novelty aspects